PENGARUH BEBERAPA EKSTRAK TUMBUHAN TERHADAP DEIGHTONIELLA TORULOSA SYD. ELLIS PENYEBAB PENYAKIT UJUNG HITAM BUAH PISANG - Joko Prasetyo dan Efri . (Universitas Lampung, 2001)
The effect of some plant extracts on Deightoniella torulosa Syd. Ellis the causative agent of black tip disease of banana. An experiment was conducted to evaluate the effect of some plant extracts on the growth and reproduction of Deightonella torulosa. The plants used in this experiments were Zingiber cassumunar, Acorus calamus, and Amomum cardamomum. The treatments of the factorial (3x4) experiment were arranged in a completely randomized design with three replicates. The first factor (plant extracts) consisted of Z. cassumunar, A. calamus, and A. cardamomum extracts. The second factor (extract concentration) consisted of 0, 100, 200, and 300 mg/l. Variables examined were the colony diameter and conidial density of D. torulosa. The result of the experiment shows that extract of Z. cassumunar, A. calamus, and A. cardamomum extracts suppressed fungal colony diameter. On Z. cassumunar and A. calamus extracts, the higher the concentration the higher fungal colony diameter suppressed. The most effective suppression by the extract was at 300 mg/l. A. calamus extract was more effective than Z. cassumunar and A. cardamomum at 100 mg/ml. Z. cassumunar and A. calamus extracts had the same effectivity at 200 mg/l, and both was more effective compared to A. cardamomum. Z. cassumunar was more effective compared to A. calamus and A. cardamomum at 300 mg/l. The results of the experiment also showed that Z. cassumunar, A. calamus, and A. cardamomum suppressed conidial production of D. torulosa. Z. cassumunar most effectively suppressed conidia production at 300 mg/l. A. calamus extract suppressed conidial production the most effectively at 200 and 300 mg/l. A. cardamomum extract significantly suppressed conidia production only at 300 mg/l. Z. cassumunar and A. calamus extracts were more effective to suppress conidia production compared to A. cardamomum for all level of concentration except control. The effectivity of Z. cassumunar and A. calamus was the same at 100 and 300 mg/l. Z. cassumunar extract was more effective than A. calamus at 200 mg/l.